Thymoquinone ameliorates lead-induced suppression of the antioxidant system in rat kidneys. Issue 1 (1st January 2016) - Mabrouk, Aymen; Cheikh, Hassen Ben
Abstract : Objective: Alteration of the antioxidant status in the kidneys may be related to lead (Pb) intoxication. The present study aimed to investigate the possible beneficial effect of thymoquinone (TQ), the major active ingredient of the volatile oil of Nigella sativa seeds, on Pb-induced renal antioxidant defense system impairment. Methods: A total of thirty two healthy adult male Wistar rats were randomly divided into four equal groups as follows: a control group, which received no treatment; a Pb group, which was exposed to 2, 000 ppm of Pb acetate in drinking water; a Pb-TQ group, which was cotreated with Pb plus TQ (5 mg/kg/day, per os ); and a TQ group receiving only TQ. All treatments were applied for five weeks. Results: TQ alone did not induce any significant changes in the antioxidant defense system. By contrast, Pb exposure significantly decreased reduced glutathione level and superoxide dismutase, glutathione peroxidase, catalase, and glutathione reductase activities in the renal tissue. Interestingly, supplementation with TQ significantly improved the affected antioxidant parameters. Conclusion: Our data are the first to provide evidence on the protective effect of TQ against Pb-induced renal antioxidant capacity impairment and suggest that this component might be a clinically promising alternative in Pb nephrotoxicity.